Effects of blanching and drying on the radical scavenging activity of natural pigments in blue ternatea (Clitoria ternatea), sugar beets (Beta vulgaris) and squash (Cucurbita maxima). - Septimo, Aileen Grace Trinidad
Effects of blanching and drying on the radical scavenging activity of natural pigments in blue ternatea (Clitoria ternatea), sugar beets (Beta vulgaris) and squash (Cucurbita maxima) were determined. The amount of the natural pigments were also determined. Significant differences in anthocyanin content among treatments differed in blue ternatea flower. Anthocyanin content in fresh, blanched and dried blue ternatea flower were 104.70±3.57 mg/L, 165.69±4.68 mg/L and 80.84±6.81 mg/L, respectively. The RSA of the anthocyanin pigment from the fresh, blanched and dried flowers were 68.00±6.15%, 84.21±68% and 86.90±2.3%, respectively. Significant differences were observed in total betalain contents in fresh (16.83 mg/L) blanched (6.99 mg/L) and dried sugar beets pulp (78.85 mg/L). Two major components of betalain (betaxanthanin and betacyanin) were also determined. Fresh sugar beets has 6.79±0.43 mg/L betaxanthin and 10.04±0.36 mg/L, blanched sample has 3.07±0.57 mg/L bexanthin and 10.04±0.36 mg/L, blanched sample has 3.07±0.57 mg/L bexanthin and 3.92±0.69 mg/L and dried sugar beets has 29.07±2.12 betaxanthin and 49.78±2.83 mg/L. The RSA of fresh, blanched and dried sugar beets were 63.50±3.73% 50.00±2.88%, and 76.56±1.49%, respectively. Significant difference in the RSA of betalain among treatments was found. Significant difference in beta-carotene among treatments were observed. Fresh, blanched, and dried were 0.8447±0.027 μg/mL, 2.329±0.19 μg/mL and 3.243±0.035 μg/mL, respectively. The RSA of beta-carotene pigment obtained from fresh, blanched and dried were 51.09±1.53%, 35.09±1.74% and 36.33±2.00%. Among the three pigments, anthocyanin from blanched blue ternatea had the highest antioxidant activity followed by the betalain from dried sugar beets and beta-carotene from fresh squash as the least.